Ethnomathematics Learning Media Based on Augmented Reality in Geometry to Improve Numeracy Skills - Salsabila, Nilza Humaira; Wulandari, Nourma Pramestie; Kurniawan, Eka (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The purpose of this research is to describe the validity of the learning media that have been developed for mathematical learning. The learning media developed were based on augmented reality to improve numeracy skills. This media also contains elements of ethnomathematics. This research is a development research using the Plomp design research model. As for one of the media criteria, it is considered eligible if it meets the valid criteria. The results of the research showed that the media expert rating showed very good classification with an average score of 50. The material expert rating indicated good classification with an average rating of 30.5. Based on the results of the research, it can be said that the learning media is declared valid.